A CH3NH3PbI3 film for a room-temperature NO2 gas sensor with quick response and high selectivity. Issue 1 (2nd January 2018) - Fu, Xianwei; Jiao, Shilong; Dong, Ning; Lian, Gang; Zhao, Tianyu; Lv, Song; Wang, Qilong; Cui, Deliang
Abstract : A room-temperature NO2 gas sensor with excellent performances is fabricated using an MAPbI3 (MA = CH3 NH3 + ) thin film. Abstract : A room-temperature NO2 gas sensor with excellent performances is fabricated using an MAPbI3 (MA = CH3 NH3 + ) thin film. It presents a high response even under extremely low NO2 concentrations. Its average response and recovery times are only ∼5 s and ∼25 s at room temperature, respectively, exhibiting its quick-responsive character. In addition, the MAPbI3 -based NO2 sensor exhibits good selectivity. Interestingly, the sensitivity of the MAPbI3 -based NO2 sensor is strikingly improved under high-pressure gas conditions. This phenomenon can be used for the online monitoring of chemical reaction processes and in situ detection of trace-level gas impurities under high-pressure conditions. Furthermore, based on theoretical calculations, a simple model is proposed to illustrate the corresponding gas-sensing mechanism.